Roles of biochar in improving phosphorus availability in soils: A phosphate adsorbent and a source of available phosphorus - Zhang, Hanzhi; Chen, Chengrong; Gray, Evan M.; Boyd, Sue E.; Yang, Hong; Zhang, Dongke (Geoderma, 2016)
In this study, the amounts of phosphorus (P) in nine types of biochar (one natural woody biochar and eight manufactured plant derived biochars) extractable by deionized water, 0.5N NaHCO3 (pH=8.5) and 0.5N H2SO4, respectively, and P adsorption on single biochar or soil/biochar mixtures were examined to investigate the potential effect and role of biochar in improving P availability in soils. Results indicated that biochars were able to bring available P into soils, but the amount and form of available P was dependent on biochar types. The results from P adsorption experiments (in phosphate solutions of 100 and 200mgPL−1, respectively) revealed that not all the biochars showed favourable P retention abilities and the amount of P retained by each biochar varied with the P concentration in the solution used. Among the nine biochars studied, only biochar derived from Mallee (Eucalyptus polybractea) at 720°C with a solid residence time of 20min showed a high P retention ability. Soils amended with Mallee biochar (5% w/w) showed an increase in the P retention ability by 16% after treatment with 200mgPL−1 phosphate solution. 55% of the retained P on Mallee biochar was still available for plant uptake. Results from the kinetic study of P adsorption on Mallee biochar indicated that there were two stages in P adsorption on Mallee biochar, a rapid chemisorption stage followed by a surface-diffusion-controlled stage when the surface adsorption sites were saturated. Scanning electron microscopy coupled with energy dispersive X-ray spectroscopy and attenuated total reflectance-Fourier transform infrared spectroscopy revealed that calcium carbonate was mainly responsible for P chemisorption on Mallee biochar. •Role of biochar in improving soil phosphorus availability was studied.•Direct phosphorus inputs from biochars vary with type of biochars.•Grass biochar contributes the highest amount of available phosphorus to soils.•Not all of biochars can be used to increase phosphorus retention in soils.•With surface calcium carbonate, Mallee biochar has the best P retention capacity.